2013
DOI: 10.1002/etc.2120
|View full text |Cite
|
Sign up to set email alerts
|

Copper tolerance and genetic diversity of Porcellionides sexfasciatus (ISOPODA) in a highly contaminated mine habitat

Abstract: Abstract-Organisms inhabiting metal-contaminated areas may develop metal tolerance, with either phenotypic adjustments or genetic changes (adaptation) or with both. In the present study, three populations of the terrestrial isopod Porcellionides sexfasciatus, collected at an abandoned mine area, were compared to assess the effects of metal contamination on tolerance to lethal and sublethal levels of copper, through comparison of survival, avoidance, and feeding. The effects of metal contamination on genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…As part of terrestrial ecosystems, terrestrial isopods have been recently used as bioindicators to assess environmental quality and show promise as invertebrates (Ghemari et al, 2018;Ghemari, Waterlot, Ayari, Douay, & Nasri-Ammar, 2019a;Khemaissia, Jelassi, Ghemari, Maryline, et al,2019;Khemaissia, Jelassi, Ghemari, Raimon, et al, 2019;Nannoni, Mazzeo, Protano, & Santolini, 2015). Furthermore they are characterized by their wide geographic distribution, they are easily collected and reared in laboratory conditions (Costa, Bouchon, van Straalen, Sousa, & Ribeiro, 2013;Godet et al, 2011;Mazzei et al, 2014;Odendaal & Reinecke, 2003). Thus, their ability to accumulate considerable amounts of MTE was demonstrated (Gäl, Markiewicz-Patkowska, Hursthouse, & Tatner, 2008;Hopkin, Hardisty, & Martin, 1986;Hopkin & Martin, 1982;Köhler, Hüttenrauch, Berkus, Gr aff, & Alberti, 1996;Mazzei et al, 2014).…”
mentioning
confidence: 99%
“…As part of terrestrial ecosystems, terrestrial isopods have been recently used as bioindicators to assess environmental quality and show promise as invertebrates (Ghemari et al, 2018;Ghemari, Waterlot, Ayari, Douay, & Nasri-Ammar, 2019a;Khemaissia, Jelassi, Ghemari, Maryline, et al,2019;Khemaissia, Jelassi, Ghemari, Raimon, et al, 2019;Nannoni, Mazzeo, Protano, & Santolini, 2015). Furthermore they are characterized by their wide geographic distribution, they are easily collected and reared in laboratory conditions (Costa, Bouchon, van Straalen, Sousa, & Ribeiro, 2013;Godet et al, 2011;Mazzei et al, 2014;Odendaal & Reinecke, 2003). Thus, their ability to accumulate considerable amounts of MTE was demonstrated (Gäl, Markiewicz-Patkowska, Hursthouse, & Tatner, 2008;Hopkin, Hardisty, & Martin, 1986;Hopkin & Martin, 1982;Köhler, Hüttenrauch, Berkus, Gr aff, & Alberti, 1996;Mazzei et al, 2014).…”
mentioning
confidence: 99%
“…However, the theory is supported by the results of a number of published studies and contradicted by the results of others. For example, no correlation was found between genetic diversity and metal pollution in the wood mouse ( Apodemus sylvaticus ) by Berckmoes et al ( 2005 ), and no correlation was found between metal exposure and the genetic variance within populations of Porcellionides saxfasciatus by Costa et al ( 2013 ). However, Berckmoes et al ( 2005 ) found contamination-related patterns in the genetic structures of wood mice at different sites.…”
mentioning
confidence: 99%
“…Likewise, terrestrial isopods, important detritivore members of soil macrofauna (Hassall & Sutton, ; Hussein, Obuid‐Allah, Mohammad, Scott‐Fordsmand, & Abd El‐Wakeil, ; Ma, Denneman, & Faber, ), are considered reliable biological indicator organisms of soil biodiversity and environmental stress (Paoletti & Hassal, ). Since they are relatively numerous and easy to collect and identify (Costa, Bouchon, van Straalen, Sousa, & Ribeiro, ; Longo, Trovato, Mazzei, Ferrante, & Oliveri Conti, ; Mazzei et al, , ), isopods became important tools for ecotoxicological studies of metal‐contaminated soils (Calhôa, Soares, & Mann, ; Drobne, ; Vijver, Wolterbeek, Vink, & Van Gestel, ). They have been shown to be able to store heavy metals from food and soil (Köhler, Hüttenrauch, Berkus, Graff, & Alberti, ; Leser et al, ).…”
Section: Introductionmentioning
confidence: 99%